Nature+ Quantitative Baseline Survey, India - International Food Policy Research Institute; Alliance of Bioversity International and the International Center for Tropical Agriculture (International Food Policy Research Institute, 2025)
In 2023, the Nature Positive Solutions (Nature+) Baseline survey was conducted in India, specifically focusing on the districts of Ahmednagar, Nashik, and Nandurbar in Maharashtra. The primary objective of the study was to assess the socio-economic conditions and agricultural systems in these regions, establishing a baseline to guide ongoing Nature+ interventions. The survey encompassed 1,228 smallholder farmer households, comprising 610 treated and 618 control households. Data collection utilized a two-stage sampling method and evaluated a range of variables, including socio-economic characteristics, agricultural practices, land use, nutrition, and the adoption of Nature+ practices. This comprehensive data will facilitate the assessment of Nature+ impacts on inclusion, poverty alleviation, food security, livelihoods, and environmental sustainability. In addition, the survey included interviews with 27 communities, gathering information on socio-demographic characteristics, access to essential services, land ownership patterns, agricultural practices, extension services, and community-wide shocks. All monetary values are reported in Indian Rupees (INR).